Enhancement of Functional Characteristics of Beneng Taro Noodles by Incorporating Garlic Nanoparticles as Bioactive Compounds - Agustina, Sri; Altisa, Reysa Previana; Rahadatul'aisy, Nadiya; Fithri, Anjenny Syfha Nabhila; Rahma, Elvira Aulia (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
Functional noodles were prepared using Beneng Taro starch and garlic nanoparticles, employing a nanocomposite technology method. The incorporation of garlic nanoparticles into the starch matrix was confirmed through FTIR analysis, which indicated an association with protein content in the functional noodles, providing health benefits. The addition of garlic nanoparticles increased the protein content of the noodles by up to 13.19% (w/w), enhancing their nutritional profile. Higher protein levels contribute to longer cooking times due to the extended denaturation process, while bioactive compounds such as allicin and flavonoids offer antioxidant and antimicrobial properties, which may reduce the risk of chronic diseases and improve overall health. Functional noodles with 2,5% (w/w) garlic nanoparticles required less than 5 minutes to cook, while concentrations of 5% and 12,5% led to cooking times of up to 17 and 30 minutes, respectively. Additionally, the bioactive compounds in garlic nanoparticles contributed to an extended shelf life by exhibiting antimicrobial and antioxidant properties. These findings highlight the potential of garlic nanoparticles to improve the nutritional and functional properties of food products, making them a promising option for health-oriented consumers.